Handbook of principles of organizational behavior : indispensable knowledge for evidence-based management - Locke, Edwin A. (Chichester, Sussex ; [Hoboken] : John Wiley & Sons, 2009)
Developed from decades of research and consulting, this international handbook identifies 30 timeless management principles every manager should know. With contributions from some of the foremost experts in organizational behavior, this insightful book demonstrates how theories of organizational behavior can be successfully applied to the workplace. With additional coverage on change, leadership, and knowledge, the new updated edition includes contributions from such notables as Teresa Amabile, Jay Conger, Fred Luthans, Antonio DeNisi, and Michael Beer.
Handbook of Principles of Organizational Behavior; Contents; Contributors and Editor; Preface by Denise Rousseau; Editor's Introduction; PART I SELECTION; PART II TRAINING AND PERFORMANCE APPRAISAL; PART III TURNOVER AND SATISFACTION; PART IV MOTIVATION; PART V TEAM DYNAMICS; PART VI LEADERSHIP; PART VII ORGANIZATIONAL PROCESSES; PART VIII ENTREPRENEURSHIP; PART IX WORK, FAMILY, TECHNOLOGY, AND CULTURE; Index.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Organizational behavior; Comportement organisationnel; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; Organizational behavior; Organisationsverhalten; Organisationspsykologi